The factors that influence the reading habit among Malaysian: a systematic literature review - Mohammed, Ahmed Sedik Hassan; Zulkifli, Zahidah; Mat Surin, Ely Salwana (Springer Nature, 2019)
Reading is an action that a person does to obtain a wider knowledge through his or her experience and this process may lead that person into a very eye-opening self-discovery. In Malaysia, reading habits rate is still at a lower level, Malaysian on average read only two books per year. About 80% of Malaysian university students are reluctant readers. They can read but choose not to read. Therefore, the objective of this study is to identify the factors affecting the reading habit among Malaysia. To answer the research question of this study we performed a systematic literature review (SLR). We defined a mapping study process adapted from existing guidelines to categorize and to structure the research evidence that has been published in the area of reading habits among Malaysian and world-wide. Twenty-Four papers were used in our synthesis of evidence, and five factors were identified. The results of this SLR showed the five factors that can affect the reading habits among Malaysian: (1) Internet (2) Environmental influence (3) Lack of motivation (4) Peer pressure (5) Entertainment. The findings of this SLR would be beneficial for understanding the needs of Malaysian towards the reading habit by looking at the factors, that might be a measurement of reading habit environment in other specific scopes.